Which one is the best-comparison of three treatment modalities in membranous glomerulonephropathy? - Khan, Mohammed Fahad; Reji, Sherin M.; Raju, Nijin Samuel; Siddini, Vishwanath; Babu, Kishore; Augustine, Rohan; Jangamani, Ravi; Shetty, Shilpa; Prakash, G. K.; Rampure, Sanjay; Ballal, Sudarshan (International Journal of Research in Medical Sciences, 2024)
Background: This retrospective study explores the efficacy of Modified Ponticelli, Rituximab and Tacrolimus in treating membranous nephropathy, focusing on remission rates. Methods: This retrospective study analyzed 41 membranous nephropathy cases treated with Modified Ponticelli, Rituximab, or Tacrolimus. Statistical analyses included Kruskal-Wallis and Chi-Square tests to evaluate treatment responses, renal markers and remission outcomes, providing comprehensive insights into treatment efficacy. Results: Modified Ponticelli demonstrated substantial reductions in proteinuria (-88.20%) and favorable increases in albumin (15.80%), outperforming Rituximab and Tacrolimus. Significant differences (p=0.0014) in remission outcomes underscore Modified Ponticelli’s efficacy, with the highest complete remission rate (26.7%) and notable partial remission rate (73.3%). Rituximab (Complete 0%, Partial 46.2%) and Tacrolimus (Complete 15.4%, Partial 30.8%) exhibited lower rates. Conclusions: In conclusion, Modified Ponticelli demonstrates superior efficacy in achieving both complete and partial remission in membranous nephropathy patients.